Quality and Shelf Life of Dressed Chicken from Different Sources under Refrigeration (4±1OC) - Kumar, H.T. Santosh; Pal, U.K.; Mandal , P.K.; Das , C.D. (Journal of Meat Science, 2016)
A study was carried out to examine the changes in quality of dressed chicken obtained from different sources of processing during storage under refrigeration at 4±1OC for 9 days. During storage at 4±1OC, pH of the samples (RSC: Road side slaughtered chicken; MSC: Market slaughtered chicken and SSC: Scientifically slaughtered chicken) decreased on day 3 of storage followed by gradual but significant (p
Keywords: Dressed chicken; Refrigeration storage; Sources of processing; Quality change